Pulse Radiolysis Studies of Collisional Deexcitation of Ne(3P1) by H2 - Khadka, Deba Bahadur (Journal of Institute of Science and Technology, 2015)
The cross sections for the deexcitation of Ne(3P1) by H2 have been measured as a function of the mean collisional energy in the range of 17.3-37.9 meV or in the temperature range from 134 K to 293 K using a pulse radiolysis method as combined with time-resolved optical absorption spectroscopy. The deexcitation cross sections are in the range of 2.1- 5.6 Å2 for Ne(3P1) and nearly constant or increase slightly with increasing the collisional energy. Journal of Institute of Science and Technology, 2014, 19(1): 75-78